Long Time Behavior of LiNi0.80Co0.15Al0.05O2 Based Lithium-ion Cells by Small Depth of Discharge at Specific State of Charge for Primary Control Reserve in a Virtual Energy Storage Plant. (November 2016) - Betzin, Christopher; Wolfschmidt, Holger; Luther, Matthias
Abstract: Lithium ion batteries play a prominent role as an energy storage device with increasing importance in various sectors. Based on reasonable power and energy density of Li-ion batteries, they occupy a huge market share on consumer market such portable electronic devices and electro mobility. Besides that, stationary applications have a strong market development. One key role could be grid support in an energy system with high share of renewable energy. In this case balancing power such as primary control reserve may utilize lithium battery systems as most promising technology because of its efficiency and cost structure. In this paper a correlation between cycling at various states of charges (SOC) and its capacity loss of commercial lithium ion batteries are shown. The investigated chemistry consists of a graphite based anode and LiNi0.80 Co0.15 Al0.05 O2 (NCA) oxide based cathode. Using cyclic voltammetry allows showing the physico chemical impact of degradation mechanism. One aspect is the change in crystal structure of the cathode material NCA by cycling around specific SOC with small depth of discharge (DOD). There is a correlation between lithium ion battery lifetime with NCA based cathode and SOC dependent cycling with small DODs, which has a huge impact on optimization battery storage systems for single or multi use cases.